Spontaneous Pneumomediastinum in COVID-19 Unrelated to Mechanical Ventilation: A Case Report - Soeroso, Noni Novisari; Soliha, Chaliza; Ghanie, Aziza; Ananda, Fannie Rizki (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Pneumo-mediastinum is a rare disease associated with barotrauma and uncommonly occurs in viral pneumonia. Although the underlying mechanism of the incidence of pneumo-mediastinum in COVID-19 patients is not fully understood, barotrauma is the most probable cause. Case Report: We reported a case of a 27-years-old woman with the chief complaint was shortness of breath and diagnosed with COVID19 based on RT-PCR examination. On the sixth day after being admitted to the hospital, suddenly, the intensity of dyspnea was increased with the decrease of oxygen saturation. CT of the chest confirmed pneumomediastinum and pneumonia COVID -19. There was no improvement of symptoms after oxygen and steroid administration. Emergency thoracotomy was not performed yet, and the patient has died. Conclusions: Although pneumomediastinum is benign disease and self-limited disease, the presents of pneumomediastinum may relate to worse outcomes in COVID19 infections.